أسلوب الإمام الدارقطني في ذكر الاختلاف في الحديث في كتابه الأفراد والغرائب: دراسة نقدية (Al-Qamar, 2024)
Imam Al-Daraqutni was among the great imams in the science of “ilm al ilal”[i] and he had a wide knowledge of hadith and their narrators, and the difference in hadith and their reason. The difference  (Ikhtilaf) may occur in the chain (Sanad) of narrators as it occurs in the text (Matan)  and the difference (Ikhtilaf)  may be influential (Muassar) or may not be influential, and if a disagreement occurs between the hadith, then we go first to combine them, and if it is not possible to combine them, then we go to the weighting of one of them, and if it is not possible to combine or weighting, then we stop until we look at Weighting clues.
Keywords: Al-Daraqutni; ilm ul ilal; Narrators; Difference in hadith; Chain; Text